Congregational faith as the final destination: Balanced scorecard as measurement tool of church performance - Feliana Zapo; Carmel Meiden (Jurnal Ekonomi Perusahaan, 2021)
In this study, the authors use the balanced scorecard to measure performance by considering the balance between the financial and non-financial, in the short and long term, that involve internal and external factors. The balanced scorecard has four perspectives. They are customer, financial, business process, and learning and growth perspectives. The authors use an ethnography approach to accompany the measurement. The research object is Church X which operates in the spiritual field. The information listed is factual that are obtained from documentation, in-depth interviews, informal interviews, and observations. This research uses a step-by-step analysis using Spradley's twelve steps applied on the domain analysis, taxonomic analysis, component analysis, and cultural theme analysis. An ethnographical adjustment is required in the analysis. The study reveals that Church X produces five cultural themes and three new multi-aspects perspectives. All the perspectives are satisfied and therefore, Church X’s performance is high.